Kondisi Terumbu Karang Di Perairan Leato Selatan Kecamatan Dumbo Raya Provinsi Gorontalo - Alfiansah, Dian; Rauf, Abdul; Yunus, Muhammad (JURNAL ILMIAH WAHANA LAUT LESTARI (JIWaLL), 2024)
Coral reefs are one of the tropical aquatic ecosystems which have a very important function both for the organisms that build this ecosystem and the surrounding ecosystems, namely seagrass ecosystems and mangrove ecosystems. Coral reef ecosystems are coastal area resources that are very vulnerable to damage, especially caused by human behavior/surrounding communities. The aim of the research is to determine the percentage of coral cover and coral reef mortality index in South Leato waters. This research was carried out from February to March 2024, located in South Leato Waters, Dumbo Raya District, Gorontalo Province. The research uses the Underwater Photo Transect (UPT) method, where the data is processed and analyzed with CPCe software. Based on the percentage of live coral cover from each station, namely Station I of 48.53% is in the medium category, Station II of 27.56% is in the medium category, Station III of 39.97% is in the medium category. With an average live coral cover of 38.69%, it is in the medium category, referring to the Decree of the Minister of Environment No. 4 of 2001 concerning Standard Criteria for Coral Reef Damage. The percentage level of coral reef damage calculated using the Mortality Index is station I at 0.46, station II at 0.66, station III at 0.67. The average mortality index for coral reefs in South Leato waters is 0.59, falling into the high mortality index category.